Rencana Kebijakan dan Program Pembangunan Hortikultura Lahan Kering untuk Provinsi Sumatera Utara: Sudah Tepatkah? - Dany Juhandi; Ardian Elonard Purba (Fakultas Pertanian, Universitas Timor, 2021)
Consumption of fruits and vegetables increases the demand of horticultural commodities but increasing of horticultural production is smaller than increasing of its demand so that imports are necessary to fill in these consumption needs. The government in 2019 plans horticultural commodities for every province in Indonesia. The objectives of this study were (1) to analyze superior horticultural commodities in North Sumatra Province, (2) to analyze the specialist and localization of horticultural commodities in North Sumatra, and (3) to compare priority horticultural commodities from the analysis results with government policy plans. Secondary data used in this study were from 2017 - 2019. The analytical tools used were Location Quotient (LQ), Specialization Quotient (SQ), and Localization Quotient (LoQ). The results showed (1) superior dryland horticultural commodities were dominated by shallots, chilies, mangoes, durian, papaya, and galangal in North Tapanuli, Toba Samosir, and Dairi Regencies, (2) several dryland horticultural commodities have a comparative advantage and its production is not localized, such as mango, durian, and chili in Batubara and Labuhan Batu Selatan Regencies, and (3) fifty percent of dry land horticultural commodities were priority commodities.